Effects of water level fluctuations on nitrogen dynamics in littoral macrophytes. (5th October 2017) - Lu, Jing; Bunn, Stuart E.; Burford, Michele A.
Abstract: Sustained water level drawdown followed by rewetting has the potential to shift macrophytes from a nutrient sink to a source, but the fate of macrophyte‐derived nutrients after rewetting is not well understood. We investigated the fate of released nitrogen (N) from isotopically labeled macrophyte litter over a 4‐week period after rewetting. We used three treatments: (1) different species in the litter (invasive Cabomba caroliniana vs. native Hydrilla verticillata ); (2) sediment desiccation history ("dried then rewetted" vs. "constantly wet"); (3) living macrophytes (presence vs. absence). Our results showed that the Cabomba litter treatment had a significantly higher percentage of macrophyte‐derived 15 N in the dissolved fraction of the water column and assimilated by phytoplankton (higher chlorophyll a concentrations), compared to the Hydrilla litter. The treatments with sediment desiccation also had a significantly higher percentage of 15 N in the dissolved fraction and used by phytoplankton after rewetting, but less in the sediment, compared to the constantly wet treatment. The presence of living macrophytes partially reduced the 15 N increase in the water column and/or sediment, but the scale of the effect was species‐ and biomass‐dependent. Our study showed that sediment pre‐desiccation changed the fate of macrophyte‐derived 15 N after rewetting, increasing the impact on water quality. This was further exacerbated by the presence of litter from an invasive species. This study highlights the need to manage water levels to maintain healthy macrophyte beds and thereby addressing water quality issues in lakes and reservoirs.